Forms of Systematization of Legal Acts - Kocharyan, Sergey (Bulletin of Yerevan University C: Jurisprudence, 2025)
The systematization of law is a permanent legal activity aimed at unifying legal acts with common features, the goals of which are to improve existing legal provisions, eliminate contradictory regulations, gaps, outdated provisions, and ensure the convenience of using legal material. Within the framework of this work, the differences and peculiarities of the forms of consolidation of legal acts have been studied, their theoretical and practical meanings have been analyzed, the effectiveness of the application of the forms existing in our legal system has been analyzed, and the need for legislative consolidation has been substantiated. As a result of the study, a grouping of systematization forms available in professional literature was also performed.